Authority of the Constitutional Court in the Dispute Resolution of Regional Head Elections - Anis Mashdurohatun; Erman Suparman; I Gusti Ayu Ketut Rachmi Handayani (Lex Publica, 2019)
Abstract Through Law No. 32 of 2004 concerning Regional Government, direct regional head elections (Pilkada) can finally be realized. In accordance with the mandate of Article 24C paragraph (1) of the 1945 Constitution, it stipulates that one of the powers of the Constitutional Court is to decide disputes over election results, which means that this includes post-conflict local election disputes. In this context, the Constitutional Court performs its role to maintain the purity of the peopleâ€™s voice if there is a voting dispute in the election process. Upholding the constitution is a form of protecting the constitutional rights of citizens and is a consequence of the adherence to the notion of constitutionalism that the 1945 Constitution chose. In this context, the constitution becomes a living constitution in the life of the nation and state. Constitutional values and norms will always be â€˜aliveâ€™ in the sense that they are constantly developing and enriched with new values and systems based on the practice of the constitution itself and real experiences in everyday life. To maintain the election process in order to achieve the expected results, it cannot rely on only one or two institutions. It requires the cooperation of all state organs, including KPU, Bawaslu, DKPP, police, prosecutors, courts, and the Constitutional Court. All these state organs must work together to make the local elections a success to maintain the sovereignty of the people. Abstrak Melalui UU No. 32 Tahun 2004 tentang Pemerintahan Daerah, pemilihan kepala daerah (Pilkada) secara langsung akhirnya dapat diwujudkan. Sesuai amanat Pasal 24C ayat (1) UUD 1945 menetapkan salah satu kewenangan Mahkamah Konstitusi adalah memutus sengketa hasil pemilu, yang berarti di dalamnya termasuk pula sengketa pemilukada. Dalam konteks inilah Mahkamah Konstitusi melakukan perannya, yaitu untuk menjaga kemurnian suara rakyat jika terdapat sengketa suara dalam proses pilkada. Penegakan konstitusi merupakan wujud dari perlindungan hak atas konstitusional warga negara, dan merupakan konsekuensi dari dianutnya paham konstitusionalisme yang dipilih oleh pembentuk UUD 1945. Dalam konteks inilah, konstitusi menjadi â€œa living constitutionâ€, dalam kehidupan berbangsa dan bernegara. Nilai dan norma konstitusi akan selalu â€˜hidupâ€™, dalam arti senantiasa berkembang dan diperkaya dengan nilai dan sistem baru, berdasarkan praktek konstitusi itu sendiri, dan pengalaman nyata dalam kehidupan sehari-hari. Untuk menjaga proses pilkada agar mencapai hasil sesuai yang diharapkan, tentu tidak dapat disandarkan kepada satu atau dua lembaga saja, dibutuhkan kerjasama seluruh organ negara, diantaranya KPU, Bawaslu, DKPP, kepolisian, kejaksaan, pengadilan, serta Mahkamah Konstitusi. Keseluruhan organ negara tersebut, harus bersinergi untuk mensukseskan pilkada demi terjaganya kedaulatan rakyat. Kata kunci: Pemilu Serentak, Mahkamah Konstitusi, Demokrasi, Indonesia